Molecular characterization of Listeria monocytogenes strains isolated from imported food in China from 14 countries/regions, 2003-2018 - Zhu, Liying; Ji, Xuejiao; Wu, Yuan; Xu, Wei; Wang, Feifei; Huang, Xinxin (Frontiers in Cellular and Infection Microbiology, 2023)
Listeria monocytogenes (Lm) is associated with severe foodborne infections and ubiquitous in the nature. Identification of characteristics of Lm transmission through trading of food products is essential for rapidly tracking Lm sources and controlling dissemination of listeriosis. In this study, a total of 44 Lm strains were isolated from food products originating from 14 countries/regions during 2003-2018 at the Shanghai Entry-Exit Inspection and Quarantine Bureau. The genomes of these Lm strains were sequenced by high-throughput sequencing. Multilocus sequence typing (MLST) analysis showed that 43 isolates were divided into 17 sequence types (STs). The distribution of STs was decentralized, with the dominant ST2 accounting for only 18.18% of the strains. The LM63 strain did not match with any of the existing STs. Coregenome MLST (cgMLST) analysis based on 1748 core genes categorized the 44 strains into 30 cgMLST types (CTs), with CT10153 and CT7892 as the most predominant CTs.Notably, LM63 and LM67 shared the same CT in the cgMLST analysis. The phylogenetic analysis based on single-copy homologous genes revealed that the 44 Lm strains were primarily classified into two lineages. The SNP analysis also indicated that these strains were roughly divided into two clades, with strains in the first clade mainly collected earlier than those in the second clade, which were predominantly collected from 2010 onwards. The analysis using the virulence factor database (VFDB) indicated that the virulence gene inlJ was the most prevalent among these 44 strains. Notably, ddrA, msbA, and sugC were enriched in this dataset, requiring further clarification of their roles in Listeria through future studies. These results might provide a clue for understanding of the global epidemiology and surveillance of Lm and present insights for implementing effective measures to reduce or prevent Listeria contamination outbreaks in imported food products.